2023
DOI: 10.1186/s41043-023-00485-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and metabolic dysfunction-associated fatty liver disease in China’s multi-ethnic regions

Xingren Zhu,
Nima Qucuo,
Ning Zhang
et al.

Abstract: Background The prevalence of metabolic dysfunction-associated fatty liver disease (MAFLD) has been rising rapidly in western China. Diet acts as an effective therapy for MAFLD. However, there has been scarce research on the association between a posteriori diet patterns (DPs) and MAFLD in this region. Method We identified three a posteriori DPs which were “Sichuan Basin pattern” characterized by a high intake of fish/seafood, poultry, fresh fruit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The results showed that both the Yunnan-Guizhou Plateau dietary pattern and the Tibetan Plateau dietary pattern were positively associated with MAFLD. Studies point to an undesirable role of salt, animal oils and high carbohydrates in the progression of MAFLD, with animal oils rich in saturated fatty acids (SFA) being positively associated with MAFLD ( 59 ).…”
Section: Lifestyle Interventions Of Mafldmentioning
confidence: 99%
“…The results showed that both the Yunnan-Guizhou Plateau dietary pattern and the Tibetan Plateau dietary pattern were positively associated with MAFLD. Studies point to an undesirable role of salt, animal oils and high carbohydrates in the progression of MAFLD, with animal oils rich in saturated fatty acids (SFA) being positively associated with MAFLD ( 59 ).…”
Section: Lifestyle Interventions Of Mafldmentioning
confidence: 99%